2013
DOI: 10.1097/hjh.0b013e32835b053d
|View full text |Cite
|
Sign up to set email alerts
|

Heredity and cardiometabolic risk

Abstract: Objectives The neuropeptide Y2 G-protein-coupled receptor (NPY2R) relays signals from PYY or neuropeptide Y toward satiety and control of body mass. Targeted ablation of the NPY2R locus in mice yields obesity, and studies of NPY2R promoter genetic variation in more than 10 000 human participants indicate its involvement in control of obesity and BMI. Here we searched for genetic variation across the human NPY2R locus and probed its functional effects, especially in the proximal promoter. Methods and results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Expression of NPY1R in adipose tissue was observed relating to the MetS components weight and insulin resistance (Sitticharoon et al, 2013 ). NPY2R (4q31) participates in modification of cardiometabolic traits (Wei et al, 2013 ), with its 21 known SNPs. Haplotypes of the proximal promoter variants G-1606A, C-599T, and A-224G disrupted predicted dependent genes, influenced the transcription of the interferon regulation factor related to IL-6, and the hepatocyte nuclear factor.…”
Section: Brain Regions Of Mets Neuroendocrine Signaling Systemsmentioning
confidence: 99%
“…Expression of NPY1R in adipose tissue was observed relating to the MetS components weight and insulin resistance (Sitticharoon et al, 2013 ). NPY2R (4q31) participates in modification of cardiometabolic traits (Wei et al, 2013 ), with its 21 known SNPs. Haplotypes of the proximal promoter variants G-1606A, C-599T, and A-224G disrupted predicted dependent genes, influenced the transcription of the interferon regulation factor related to IL-6, and the hepatocyte nuclear factor.…”
Section: Brain Regions Of Mets Neuroendocrine Signaling Systemsmentioning
confidence: 99%
“…Recent results have indicated that naturally occurring genetic variation at the Y 1 R locus has implications for heritable autonomic control of the circulation and hypertension, suggesting novel pathophysiological links among the Y 1 R locus, autonomic activity, and BP [ 8 ]. Y 2 R expression is upregulated in spontaneously hypertensive rats [ 9 ] and endogenous expression of Y 2 R is also documented in neuroendocrine cells and neuroendocrine tissues including the brainstem of a rodent model of hypertension [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, NPY is primarily produced in the arcuate nucleus, with its orexigenic effects manifesting in the paraventricular nucleus, thereby inducing hunger, lowering energy expenditure, and contributing to obesity [ 11 ]. Some of the NPY receptors mediate neuroendocrine effects and, among these, NPY1R expression in fat cells is associated with the development of MetS by promoting insulin resistance and fat mass accumulation, whereas some variants of NPY2R may influence cardiometabolic traits [ 11 , 79 , 80 , 81 ]. In addition, the gene NPY2R (4q31) plays a crucial role in an animal model of MetS, causing abdominal fat deposition and angiogenesis in adipose tissue in response to sympathetic nerve stimulation in response to social or environmental stress [ 11 , 82 ].…”
Section: The Regulation Of Satiety and Hunger In Central Neuroendocri...mentioning
confidence: 99%